EFFECT OF DIFFERENT PROCESSING METHODS ON THE PROXIMATE COMPOSITION, MINERAL, AND ORGANOLEPTIC PROPERTIES OF DOMESTICATED GRASSCUTTER (Thryonomys swinderianus) - Adebowale, Taiwo K.; Ibiyomi, B. B.; Akintunde, O. A.; Oduntan, O. O.; Ajibade, T. B. (FUDMA JOURNAL OF SCIENCES, 2024)
Wildlife plays a crucial role in supplying energy, protein, and various components essential for human diets in tropical regions. In urban areas, there is still substantial consumption of bush meat, such as grasscutter, which serves as a significant source of nutrition. The study examined the proximate composition, mineral content, and sensory properties of processed grasscutter (Thryonomys swinderianus) meat using three distinct preparation methods. The grasscutter samples were acquired from the Department of Forestry and Wildlife Management at the Federal University of Agriculture, Abeokuta, Nigeria. The meat underwent smoking, boiling, and oven drying after slaughtering and washing. A portion of each processed grasscutter meat was collected, placed in sterile containers, and transported to the laboratory for proximate and mineral analysis. A questionnaire was employed for organoleptic evaluation and twelve taste panelists comprising randomly selected students, non-academic staff members, and lecturers from the department participated in the assessment. The proximate analysis followed the standard procedure outlined in the AOAC method (2005). Results indicated that the crude protein content was 20.06% for smoked and 16.40% for oven-dried grasscutter meat. The oven-dried meat exhibited lower fat content. Sensory evaluation suggested that oven-dried meat was perceived as the most favorable, with the highest mean values for aroma (8.42±0.26), taste (7.67±0.36), flavor (8.42±0.99), texture (7.67±0.36), acceptability (7.67±0.36), and the lowest for odor (2.08±0.31) compared to boiled and smoked samples. Moreover, oven-dried grasscutter meat demonstrated elevated levels of magnesium (7.45%) and potassium (27.43%). It is therefore recommended that the oven drying method of meat processing should be...